2019
DOI: 10.1021/acsmacrolett.9b00216
|View full text |Cite
|
Sign up to set email alerts
|

Induced Circular Dichroism of Isotactic Poly(2-vinylpyridine) with Diverse and Tunable “Sergeants-and-Soldiers” Type Chiral Amplification

Abstract: Facile and efficient construction of the helical structure with diverse and tunable chiral amplification from an achiral polymer is attractive but remains a challenge to develop multiple functional materials. We report herein a macromolecular acid−base complex of highly isotactic poly(2vinylpyridine) (mmmm > 99%), (+)-camphorsulfonic acid, and dodecylbenzensulfonic acid. The asymmetric induction of the chiral additive through the ionic interactions between pyridinium pendants and acid ions drives the polymer b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…These interactions forced the polymer backbone to twist in a preferred handedness manner in CHCl 3 and the mixed solvent CHCl 3 /CH 3 CN. [ 19 ] It was demonstrated that many factors including the base to acid ratio, chiral‐acid content, and solvent nature could influence the induced chirality. In addition, by tuning the solvent composition, four distinct types of “sergeants‐and‐soldiers” effect were observed within a single system for the first time, due to the sensitivity of ionic interactions to solvent polarity.…”
Section: Supramolecular Chirality Transfer In Solution Systemsmentioning
confidence: 99%
“…These interactions forced the polymer backbone to twist in a preferred handedness manner in CHCl 3 and the mixed solvent CHCl 3 /CH 3 CN. [ 19 ] It was demonstrated that many factors including the base to acid ratio, chiral‐acid content, and solvent nature could influence the induced chirality. In addition, by tuning the solvent composition, four distinct types of “sergeants‐and‐soldiers” effect were observed within a single system for the first time, due to the sensitivity of ionic interactions to solvent polarity.…”
Section: Supramolecular Chirality Transfer In Solution Systemsmentioning
confidence: 99%
“…P4‐4‐ L ‐CA was first used as the additive for the resolution of racemic threonine ( rac ‐Thr, a typical conglomerate forming racemate) [9] to verify our ideas. 1 H‐NMR spectroscopy confirmed the formation of ionic bonds between pyridine units ( pK a =8.10) and sulfonic acid groups ( pK a1 =1.55) of L ‐cysteic acid ( L ‐CA) (Figure S1 and S3) [10] . Stoichiometric complex was obtained when an equal molar or excessive amount of L ‐CA was added (Figure S2).…”
Section: Figurementioning
confidence: 86%
“…Electronic circular dichroism (ECD) is not the most common method to study self-assembly, but numerous studies have demonstrated that it can address various problems, ranging from the definition of simple stoichiometric ratios between the partners, giving rise to a supramolecular structure to the derivation of thermodynamic parameters, or ultimately to the refinement of a structure for a complex or an aggregate [ 2 , 3 , 4 , 5 ]. The ECD technique has been found particularly useful for the determination of chirality amplification during self-assembly of supramolecular polymers (according to the “sergeants-and-soldiers” rule) [ 6 , 7 ] and for studying host–guest complexation by induced chirality effects [ 8 ]. Despite numerous advantages, the information encoded in ECD spectra is typically difficult to be assessed directly because the ECD spectra include the contributions of all conformers populated at the working temperature [ 9 , 10 ], and prediction of the spectrum even for a single conformer typically requires quantum calculation.…”
Section: Introductionmentioning
confidence: 99%